A MATLAB-based GUI for remote electrooculography visual examination - Štula, Tomáš; Proto, Antonio; Kubíček, Jan; Peter, Lukáš; Černý, Martin; Penhaker, Marek (Lékař a technika, 2020)
In this work, a MATLAB-based graphical user interface is proposed for the visual examination of several eye movements. The proposed solution is algorithm-based, which localizes the area of the eye movement, removes artifacts, and calculates the view trajectory in terms of direction and orb deviation. To compute the algorithm, a five-electrode configuration is needed. The goodness of the proposed MATLAB-based graphical user interface has been validated, at the Clinic of Child Neurology of University Hospital of Ostrava, through the EEG Wave Program, which was considered as "gold standard" test. The proposed solution can help physicians on studying cerebral diseases, or to be used for the development of human-machine interfaces useful for the improvement of the digital era that surrounds us today.
Keywords: lidé; User-Computer Interface; software; Adult; mrkání; technologie sledování pohybu očí; Eye Movements; pohyby očí; Blinking; Eye Movement Measurements; Electrooculography; Eye-Tracking Technology; Humans; Research; měření pohybů očí; Software; uživatelské rozhraní počítače; mužské pohlaví; elektrookulografie; Matlab; Male; dospělí; výzkum